The Principle of Universality in Cross-Border Insolvency Disputes - Arivan Halim; Elizabeth Irianti Mayangsari Runtu (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Cross-border bankruptcy cases often involve legal processes in various jurisdictions, such as those between FM and its creditors in Indonesia and Saudi Arabia, and between Bankrupt Debtors and Curators in Singapore. This underscores the need for harmonization of cross-border bankruptcy laws. The principle of universality in cross-border bankruptcy disputes becomes crucial to address this issue. This research aims to analyze the philosophical foundation of the universality principle in cross-border bankruptcy disputes and how this principle is applied in various international legal instruments and applicable laws and regulations in Indonesia. The research method used is a normative juridical approach, examining various international legal instruments such as the UNCITRAL Model Law and European Council Regulation No. 1346/2000, as well as relevant national legislation. Data were collected through literature review and analysis of legal documents. The universality principle allows for recognition and cooperation among countries in resolving cross-border bankruptcy disputes, thus enabling the efficient and fair administration of debtor's bankruptcy assets worldwide. The application of this principle provides benefits such as debt settlement certainty, more secure asset organization, lower administration costs, better dispute resolution predictions, and fairer debt settlement distribution. However, there are also criticisms regarding foreign laws governing domestic relationships and uncertainty in determining the debtor's home country. Concrete cases in Indonesia and Singapore demonstrate how the universality principle is applied in practice, with Singapore adopting the UNCITRAL Model Law on Cross-Border Insolvency and the Philippines preparing the Corporate Recovery Act to accommodate international business developments.